The effects of bar holder material, cantilever and vertical misfit on stresses in implant supported overdentures: Three dimensional finite element analysis - Kaymak Sümeyra; Yerliyurt Kaan (Balkan Stomatological Society, 2022)
Background/Aim: The aim of this study is to examine with finite element analysis the distal bar extension, the bar substructure material type and the amount of bar substructure-abutment mismatch, and the stress caused by the implant at the surrounding bone tissue in bar-retained prostheses. Material and Methods: A bar-retained prosthesis model has been designed on three implants placed in the fully toothless lower jaw at the places of both canines and the midline. Bar holder according to distal cantilever lengths was modeled to be 0 mm, 8 mm and 14 mm. The vertical incompatibility of the bar holder substructure with the abutment was modeled to be 0 µm, 100 µm and 200 µm. A total of twenty-seven (3x3x3) different models were obtained with three different bar infrastructure materials (titanium, gold and chromium-cobalt). 150 N occlusal force was applied to the central fossa of the left 1st molar tooth with a rigid food stuff. Results: In the cortical bone, the highest maximum principle stress value (2.78 MPa) was analyzed around the anterior implant socket in the model 13 (gold, cantilever 0mm, misfit 100 µm). The highest von Mises stress value (343.43 MPa, which occurred at the selected joints in bar holders) was observed in model 27 (chrome-cobalt, cantilever 14mm, misfit 200 µm). Conclusions: When the length of the cantilever is 14 mm, it causes a significant increase in stress around the implant, especially near the cantilever. It has been observed that bar infrastructures with high elastic modulus create higher stress values.